CHALLENGES OF HACCP IMPLEMENTATION IN AGRICULTURAL FOOD PRODUCTS IN THAILAND (GEOMATE Journal, 2016)
Agricultural food industry in Thailand generated incomes about 10.5% gross domestic product (GDP) of the country in 2015. The demands of agricultural food products around the world has been increased for years. Agricultural food products from Thailand could not be exported as many as the growth of market demands because of the limitation of food safety guarantees. Analysis and Critical Control Points (HACCP) is a minimal requirement for exported food products to assure food safety. Not all Thai companies in agricultural food industry received HACCP certifications. There might be some challenges that obstructed the implementation of HACCP in the food industry of Thailand. The objective of this research was to identify challenges faced by companies in Thailand when implementing the HACCP in agricultural food companies. An online survey was conducted to collect data from companies in food industry. Twenty companies completed the survey. All twelve challenges proposed in the research survey were experienced by participating companies during the HACCP implementation. The challenges, identified as barriers to implement HACCP, were a lack of employee engagement in HACCP implementation, a lack of employees who understand the HACCP system, and a lack of advanced statistical knowledge. The results suggested companies to develop an effective communication plan to convey the HACCP implementation plan to employees at all levels and to provide training programs, related to HACCP and statistics, to fulfill knowledge and skills required in the HACCP implementation.